The game as an activator of compositional state in dance (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
It reflects on improvisation in dance, more specifically the game as the achievement of a state of the dancing body enabled to create. It addresses the nature of the Game as an aspect of culture in its most varied forms. The improvisation to which the research refers emerges from the context of postmodern dance and is disseminated with a wide range of methodological possibilities. It constitutes a composition process to generate choreographic material, as an event in dance and/or as a proposal for real-time composition performance. It considers the role of the choreographer and/or director based on approaches to scene creation.
Keywords: co-composition; improvisation; game; contemporary dance; proposition